Summer undergraduate biomedical research program for underrepresented minority students in a rural, low-income state - Michael E. Anders; Latrina Y. Prince; Tremaine B. Williams; Robert E. McGehee; Billy R. Thomas; Antino R. Allen (Frontiers Media S.A., 2024)
IntroductionDiversity can enhance the agenda and quality of biomedical research, but a dearth of underrepresented minorities and women serve as biomedical researchers. The study purpose was to examine the impact of the a summer undergraduate research program on self-efficacy in research, scientific communication, and leadership as well as scientific identity, valuing objectives of the scientific community, and intent to pursue a biomedical research career.MethodsUnderrepresented minority and female undergraduate students participated in a mentored research experience in a rural, low-income state.ResultsStudents' self-efficacy in research, scientific communication, and leadership as well as scientific identity, valuing objectives of the scientific community, and intent to pursue a biomedical research career increased post-program compared to pre-program.ConclusionThis study supports implementation of a biomedical summer undergraduate research program for URM and women in a poor, rural, settings.